2019
DOI: 10.5009/gnl18296
|View full text |Cite
|
Sign up to set email alerts
|

Depression Promotes the Onset of Irritable Bowel Syndrome through Unique Dysbiosis in Rats

Abstract: Background/Aims Although studies using conventional animal models have shown that specific stressors cause irritable bowel syndrome (IBS), it is unclear whether depression itself causes IBS. Our aim was to establish a rat model to determine if depression itself promotes the onset of IBS and to elucidate the role of gut microbiota in brain-gut axis pathogenesis during coincident depression and IBS. Methods Rat models of depression were induced using our shuttle box metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…The use of questionnaires does not focus on this relationship and the long-term observation time needed precludes conclusions as regards to the onset of disease or symptoms. Animal models may be useful to reveal possible etiological factors related to the onset of gastrointestinal symptoms [50][51][52].…”
Section: Discussionmentioning
confidence: 99%
“…The use of questionnaires does not focus on this relationship and the long-term observation time needed precludes conclusions as regards to the onset of disease or symptoms. Animal models may be useful to reveal possible etiological factors related to the onset of gastrointestinal symptoms [50][51][52].…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al (2017) similarly found that severe depressive symptoms were associated with a high odds ratio for IBS [ 40 ]. Empirical evidence also indicates that psychosomatic symptoms, such as depression, result in a two-fold increase in the onset of gastrointestinal symptoms in IBS [ 44 , 45 ].…”
Section: Irritable Bowel Syndrome and Depressionmentioning
confidence: 99%
“…We performed high‐throughput sequencing of gut microbiota by using the cecal contents in the same way as described in our previous study 19 …”
Section: Methodsmentioning
confidence: 99%
“…Leukocytes were isolated from the spleen. Leukocytes were labeled with carboxyfluorescein diacetate succinimidyl ester (CFSE, Thermo Fisher Scientific, Waltham, MA, USA) at the concentration of 15.6 μM 19 . In some experiments, leukocytes were incubated with the antibody for β 7 integrin (FIB27, BD PharMingen) at a concentration of 100 μg/mL before fluorescent staining.…”
Section: Methodsmentioning
confidence: 99%